Breaking of Internal Waves and Turbulent Dissipation in an Anticyclonic Mode Water Eddy - Fernandez Castro, Bieito; Evans, Dafydd Gwyn; Frajka-Williams, Eleanor; Vic, Clément; Naveira-Garabato, Alberto C (Journal of Physical Oceanography, 2020)
A four-month glider mission was analyzed to assess turbulent dissipation in an anticyclonic eddy at the western boundary of the subtropical North Atlantic. The eddy (radius ≈ 60 km) had a core of low potential vorticity between 100–450 m, with maximum radial velocities of 0.5 m s−1 and Rossby number ≈ −0.1. Turbulent dissipation was inferred from vertical water velocities derived from the glider flight model. Dissipation was suppressed in the eddy core (ε ≈ 5×10−10 W kg−1) and enhanced below it (> 10−9 W kg−1). Elevated dissipation was coincident with quasi-periodic structures in the vertical velocity and pressure perturbations, suggesting internal waves as the drivers of dissipation. A heuristic ray-tracing approximation was used to investigate the wave-eddy interactions leading to turbulent dissipation. Ray-tracing simulations were consistent with two types of wave-eddy interactions that may induce dissipation: the trapping of near-inertial wave energy by the eddy’s relative vorticity, or the entry of an internal tide (generated at the nearby continental slope) to a critical layer in the eddy shear. The latter scenario suggests that the intense mesoscale field characterizing the western boundaries of ocean basins might act as a ‘leaky wall’ controlling the propagation of internal tides into the basins’ interior.